2016
DOI: 10.3389/fpls.2016.00846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intercropping with Potato Onion on the Growth of Tomato and Rhizosphere Alkaline Phosphatase Genes Diversity

Abstract: Background and Aims: In China, excessive fertilization has resulted in phosphorus (P) accumulation in most greenhouse soils. Intercropping can improve the efficiency of nutrient utilization in crop production. In this study, pot experiments were performed to investigate the effects of intercropping with potato onion (Allium cepa L. var. aggregatum G. Don) on tomato (Solanum lycopersicum L.) seedlings growth and P uptake, the diversity of rhizosphere phosphobacteria and alkaline phosphatase (ALP) genes in phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…This finding differs from conventional views, because rhizosphere microbial communities are generally less diverse than those in bulk soil [51,52]. In the intercropping systems, however, root microbiota often show a higher diversity [53,54]. Depending on microbial substrate preferences, secondary metabolites of plants shape the rhizosphere microbial community [11].…”
Section: Ethylene Chemically Regulates Rhizosphere Microbial Diversitmentioning
confidence: 90%
“…This finding differs from conventional views, because rhizosphere microbial communities are generally less diverse than those in bulk soil [51,52]. In the intercropping systems, however, root microbiota often show a higher diversity [53,54]. Depending on microbial substrate preferences, secondary metabolites of plants shape the rhizosphere microbial community [11].…”
Section: Ethylene Chemically Regulates Rhizosphere Microbial Diversitmentioning
confidence: 90%
“…DNA fragments of the V3-V4 region of the bacterial 16S rRNA gene were amplified using the primer pair 341F (5 -CCTACGGGNGGCWGCAG-3 ) and 805R (5 -GACTACHVGGGTATCTAATCC-3 ) fused with Illumina MiSeq adapters and a 6-bp barcode sequence unique to each sample [15,39]. PCR amplifications were carried out in triplicate in 50-”L reactions containing 10 ng of genomic DNA.…”
Section: Pcr Amplification and Miseq High-throughput Sequencingmentioning
confidence: 99%
“…Rarefaction and rank-abundance curves were generated at a 97% OTU similarity level. Statistical analysis was performed using analysis of variance (ANOVA) with p values to determine whether the diversity indexes were statistically significant among the rhizosphere soil samples [39]. To estimate beta diversity, the similarities of the members and structures of the microbiotas were calculated by utilizing the weighted and unweighted UniFrac distances from the normalized OTU tables for the various samples [42].…”
Section: Data Processing and 16s Rrna Gene-based Community Analysismentioning
confidence: 99%
“…In our previous studies, we found that potato onion is an effective partner for intercropping and relay intercropping. Intercropping with potato onion increased the growth of tomato seedlings and changed tomato root architecture (Wu et al 2016;Yu et al 2017) and the root exudates of potato onion has facilitating effects on tomato seedlings (Liu et al 2013). To date, however, the effects of potato onion leaf volatiles and leachates have remained virtually unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of facilitating interactions between plant species has received increased attention (Moeller 2004;Zhang and Li 2003) and the facilitating interactions have also been used for crop growth regulation (Batish et al 2001;Narwal and Zeng 2010). For example, potato onion, as a companion plant, can increase the growth of cucumber and tomato (Yang et al 2011;Liu et al 2013;Wu et al 2016). The mechanisms whereby the effects of facilitating interactions are mediated are various and the release of chemicals is one of the reasons (Inderjit et al 2011).…”
Section: Introductionmentioning
confidence: 99%